Acute and chronic effects of foam rolling vs eccentric exercise on ROM and force output of the plantar flexors. Issue 2 (17th January 2019) - Aune, Anne A. G.; Bishop, Chris; Turner, Anthony N.; Papadopoulos, Kostas; Budd, Sarah; Richardson, Mark; Maloney, Sean J.
ABSTRACT: Foam rolling and eccentric exercise interventions have been demonstrated to improve range of motion (ROM). However, these two modalities have not been directly compared. Twenty-three academy soccer players (age: 18 ± 1; height: 1.74 ± 0.08 m; body mass: 69.3 ± 7.5 kg) were randomly allocated to either a foam rolling (FR) or eccentric exercise intervention designed to improve dorsiflexion ROM. Participants performed the intervention daily for a duration of four weeks. Measurements of dorsiflexion ROM, isometric plantar flexion torque and drop jump reactive strength index were taken at baseline (pre-intervention) and at three subsequent time-points (30-min post, 24-hours post and 4-weeks post). A significant time x group interaction effect was observed for dorsiflexion (P = 0.036), but not for torque or reactive strength index. For dorsiflexion, there was a significant increase in both acute (30-min; P < 0.001) and chronic (4-week; P < 0.001) ROM for the eccentric group, whilst FR exhibited only an acute improvement (P < 0.001). Eccentric training would appear a more efficacious modality than foam rolling for improving dorsiflexion ROM in elite academy soccer players.